Simulations of the scaled reactor cavity cooling system experimental facility with flownex - Sena, Marcos Salomão de (2023)
The scaled Water-cooled Reactor Cavity Cooling System (WRCCS) experimental facility reproduces a passive safety feature to be implemented in Generation IV nuclear reactors. It keeps the reactor cavity and other internal structures in operational conditions by removing heat leakage from the reactor pressure vessel. The present work used Flownex to model the facility and predict the experimental thermal-hydraulic behavior. Three representative steady-state cases defined by the bulk volumetric flow rate were simulated (Re = 2,409, Re = 2,490, and Re = 11,524). Flownex predictions of the cavity outlet temperature, risers’ temperature profile and flow rate split were compared with the experimental data and previous RELAP simulations. The comparisons are in reasonable agreement with previous studies, demonstrating the ability of Flownex to simulate the RCCS behavior. For the low Re cases, temperature and flow split across the risers are evenly distributed. Conversely, there’s an asymmetry trend in both temperature and flow distributions for the high Re case. Additionally, a sensitivity analysis was performed using the Re = 2,409 case to assess the impact on the system’s temperature and flow due to power reduction transferred to the risers. The results showed very good adherence to the RELAP studies. Finally, a loss of secondary coolant scenario was conducted. Although Flownex employs a two-phase homogeneous mixture model, the global behavior of the average system’s parameters reasonably agrees with predictions by previous studies in RELAP.